2017
DOI: 10.1111/asj.12800
|View full text |Cite
|
Sign up to set email alerts
|

Leisure riding horses: research topics versus the needs of stakeholders

Abstract: Horses intended for leisure riding do not undergo any selection and most often retired sports horses or defective horses are chosen, as a low selling price determines their purchase by a leisure riding center. Unfortunately, horses bought at low prices usually have low utility value, are difficult to handle, require a special or individual approach and do not provide satisfaction in riding. However, neither modern horse breeding nor scientific research address the need to breed horses for leisure activities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
8
0
5
Order By: Relevance
“…Various studies indicated an incidence of fractures in races between 1–2% per race start [2, 4, 5], with pelvic and tibial stress fractures identified as the most common cases of fracture [5]. Furthermore, the number of horses used in leisure sports is still increasing and includes a trend towards free-range husbandries in groups leading potentially to injuries and contortions especially in the fetlock area [6, 7]. Similar to treatment in humans, current strategies towards long bone fractures in horses focus on stabilization of the fracture site by means of screws or nails [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicated an incidence of fractures in races between 1–2% per race start [2, 4, 5], with pelvic and tibial stress fractures identified as the most common cases of fracture [5]. Furthermore, the number of horses used in leisure sports is still increasing and includes a trend towards free-range husbandries in groups leading potentially to injuries and contortions especially in the fetlock area [6, 7]. Similar to treatment in humans, current strategies towards long bone fractures in horses focus on stabilization of the fracture site by means of screws or nails [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The research was conducted on the leisure horses. Horses in leisure usage, which is recreation, differ sports usage, considered as competitive in Olympic disciplines on different levels, and racing usage, considered as participating in races [9,10]. The difference between sports or racing usage and leisure usage may be defined based on determining the activity initiator and the purposes of training.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of problems with leisure horses often result from their owner's lack of experience or knowledge (Hemsworth, Jongman, & Coleman, 2015). In Janczarek and Wilk's (2017) opinion as well as ours, riding utilization of the leisure horse, back mobility and overload needs to be determined with modern technology and methods similar to those used for sports horses.…”
mentioning
confidence: 95%
“…In equestrian sport or racing, similar to each sports discipline, the correlation between achieved results and the activity on a leisure level is observed. However, sports usage, considered as competitive in Olympic disciplines on different levels, and racing usage, considered as participating in races, differs from leisure usage, which is recreational (Daly, ; Janczarek & Wilk, ). The difference between sports or racing riding and leisure riding may be defined based on determining the activity initiator and the purposes of training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation